Exit timing of venture capitalists in the course of an initial public offering - Werner Neus; Uwe Walz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
We analyze the desinvestment decision of venture capitalists in the course of an IPO of their portfolio firms. The capital market learns of the project quality only in the period following the IPO. Venture capitalists with high-quality firms face a trade-off between immediately selling their stake in the venture at a price below the true value and having to wait until the true value is revealed. We show that the dilemma may be resolved via a reputation-acquiring mechanism in a repeated game set-up. Thereby, we can explain, e.g., the advent of 'hot-issue market behavior' involving early disinvestments and a high degree of price uncertainty. Furthermore, we provide a new rationale for underpricing. Young venture capitalists may use underpricing as a device for credibly committing themselves to acquiring reputation.
urn:nbn:de:hebis:30-9972
Keywords: G24; G14; D82; 330; Exit Decisions; Venture Capital; IPO; Underpricing